Clinicopathologic Characteristics of EGFR Mutations in Non-Small Cell Lung Cancer (NSCLC) in Central New York - Zaccarini, MD, Daniel J.; Depasquale, MD, Brittany; Poudel, MD, Aarati; Graziano, MD, Steven; Zhang, MD, Ph D, Shengle (North American Journal of Medicine and Science, 2018)
EGFR mutation rates in NSCLC differ among ethnic groups, nations, age, sex, smoking status, and histologic differentiation. We examined the clinicopathologic characteristics of EGFR mutations in NSCLC in the Central New York (CNY) region for the first time, to further characterize the disease and facilitate management. 7.1% (33/464) NSCLCs were positive for EGFR mutations. Based on available clinical data, EGFR positive mutation status was found in 7.4% (28/380) White, 5.3% (2/38) African American, 0% (0/4) American Indian/Alaska native, 33.3% (1/3) Asian/Pacific, 0% (0/2) Hispanic, and 0% (0/1) Asian/Indian patients. Average age in EGFR positive cases was 68.3 years and 66 in negative cases (p>0.05). Prevalence of EGFR mutations was 9.2% in females and 4.4% in males (p<0.05); 37.9% in never-smokers and 4.4% in ever-smokers (p<0.05). Poorly differentiated adenocarcinoma was seen in 16.7% (4/24) of EGFR positive cases and 43.4% (105/242) of negative cases (p < 0.05). Solid pattern was seen in 9.0% (2/22) of positive cases and 33.3% (44/132) of negative cases (p < 0.05). The acinar pattern was the most common pattern seen in adenocarcinomas with exon 19 deletion, and exon 21 (L858R) mutations. Therascreen detected four additional rare mutations (1 T790M, 1 L861Q, G719X, and 1 exon 21 insertion) in 238 cases, increasing overall EGFR detection rate from 6.3% to 7.1%. EGFR mutation prevalence in NSCLC in CNY (7.1%) was lower than the global average in a recent review (13.9% [10.3-36.4]), likely due to predominantly white population in this study, accounting for 84.8% (28/33) of positive cases in CNY. Similar to previous studies, positive EGFR mutation status was more frequent in females and never-smokers, and less prevalent in adenocarcinoma with poor differentiation or solid growth. [N A J Med Sci. 2018;11(1):1-5. DOI: 10.7156/najms.2018.110101]